Three-phase AC Induction Motor Speed Control Based on Variable Speed Driver - mohammed, abdelrahim ahmed, ate; Gafar, Rihab; Sun, Xiuyun; Abozead, Tahleel (UI Scholars Hub, 2022)
Massive loss of power is a concern for many countries because of the high power consumption of alternating current (AC) motors. The motor speed should be controlled to alleviate this problem and save more power. This paper proposes a simple simulation for a variable speed driver (VSD) to control the three-phase induction motor speed. The VSD consists of three parts. The converter performs from full bridge diodes to convert single-phase AC voltage into direct current voltage, and then this voltage is filtered by the RL filter and transferred to the last part, which is the inverter. The model was simulated by using MATLAB/Simulink. Findings show that the VSD controller provides sufficient control over the AC induction motor speed.